Our little farm : adventures in sustainable living - Wohlleben, Peter, 1964-; Wohlleben, Miriam; Billinghurst, Jane, 1958- (Greystone Books : David Suzuki Institute, 2023)
"Peter and Miriam moved from the city to a remote forest lodge in the early nineties. Amidst juggling careers and raising a young family, they learned how to plant and rotate crops, harvest and preserve nature's bounty, and tend to the unique needs of their animals and environment. Along the way, they made mistakes and abandoned some projects (sheep raising was not their thing) but maintained a sense of joy in their shared goal. Brimming with insights, wisdom, and tips on everything from constructing farm buildings to choosing the perfect chicken, Our Little Farm shows that, with a little grit, humor, and self-compassion, it's possible to live according to our values and to care for the earth even as we care for ourselves, our homes, and our families. Published in partnership with the David Suzuki Institute."--